MODIFIKASI BUCKET ELEVATOR 536 PADA PT X - Candra Damis Widiawaty; Averoes Syahputra Agil; Bayu Chandra Hangesthi (Politeknik Negeri Jakarta, 2019)
In the production process at PT X, such as casting process, required raw material in the form of casting sand. The sand transport process is done by a machine called a Bucket Elevator. The current condition of Bucket Elevator at Plant 2 PT X had some problems on its design due to the initial modification process to the machine that were deliberately done in order to ease the process of troubleshooting and repair on the machine to adjust the height of the drum shaft supported by the bearing, however, the modification causes a sand leak that impacted the lifetime of the bearing. The damage that occurs to the bearing of the Bucket Elevator can slow the production process at PT X down, which lasts between 120 hours to 134 hours per week. Therefore, it is necessary to modify the design of the Bucket Elevator machine in order to stop the sand leakage and be able to work optimally. The design modifications made, are changes to the shaft height adjusting mechanism of the Bucket Elevator 536 drum machine by providing a lock to minimize the leakage of sand that occurs and replace the bearing type to the type that is equipped with a seal to prevent the entry of sand into the bearings. The result of this modification can extend the lifetime bearing, thereby reducing production costs due to bearing replacement, and easing the troubleshooting and repairing process of the engine to adjust the height of the drum shaft supported by the bearings.